(untitled) (Rupandehi Campus Journal, 2025)
This paper examines Amitav Ghosh’s The Great Derangement: Climate Change and the Unthinkable through the framework of Constitutive Rhetoric. It analyzes how the author not only raises awareness about environmental degradation but also critiques the socio-political structures that marginalize vulnerable communities. Ghosh’s narrative positions the Global South—particularly Asian nations—as central to the discourse on climate justice, calling for their active inclusion in global climate action. Through rhetorical strategies that evoke collective memory, ecological and cultural identity, the paper argues that Ghosh constructs an eco-conscious subjectivity that challenges dominant Western narratives. The analysis reveals that Ghosh’s eco-narrative functions as a rhetorical call-to-action, aiming to boost a globally inclusive and culturally resonant form of environmental advocacy.